2019
DOI: 10.1002/ijc.32805
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative exposure to premenopausal obesity and risk of postmenopausal cancer: A population‐based study in Icelandic women

Abstract: Obesity, often assessed at one point in time, is an established risk factor of several types of cancer, however, associations with cumulative exposure to obesity across the life course are not well understood. We investigated the relationship between combined measures of duration and intensity of premenopausal overweight and obesity and the incidence of postmenopausal breast, endometrial, and colorectal cancers in Icelandic women. Body mass index (BMI) trajectories between ages 20 and 50 of 88,809 women from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, a 2017 meta-analysis by Chen and colleagues showed no association between increased BMI and a premenopausal breast cancer diagnosis (3), and a 2019 systematic literature review and meta-analysis by the World Cancer Research Fund International found an overall inverse association between BMI and a premenopausal breast cancer diagnosis but noted variability across regions; although European studies showed inverse associations, North American studies showed nonsignificant or inverse associations, and Asian studies showed positive associations (8). Studies evaluating the association between premenopausal BMI and future breast cancer (including breast cancers that may occur after the menopausal transition) show mixed results (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, a 2017 meta-analysis by Chen and colleagues showed no association between increased BMI and a premenopausal breast cancer diagnosis (3), and a 2019 systematic literature review and meta-analysis by the World Cancer Research Fund International found an overall inverse association between BMI and a premenopausal breast cancer diagnosis but noted variability across regions; although European studies showed inverse associations, North American studies showed nonsignificant or inverse associations, and Asian studies showed positive associations (8). Studies evaluating the association between premenopausal BMI and future breast cancer (including breast cancers that may occur after the menopausal transition) show mixed results (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The findings in our study were consistent with these previous studies when BMI was considered only at a single point of time. However, few studies have evaluated the associations looking at BMI at various points of time during the life span . We considered BMI at various decennial ages and found excess weight at all decennial ages between 20 and 70 years to be associated with CRC risk in a clear dose-response manner.…”
Section: Discussionmentioning
confidence: 99%
“…The lower proliferation status of breast glandular epithelial cells of O women may be partly due to cell cycle arrest, leading to cellular senescence. Promotion of senescence has been ascribed to IL10 in a number of cell types (Novakova et al 2010, Huang et al 2018. To examine the possibility that breast adipose-associated IL10 expression is correlated with glandular epithelial cell senescence in the context of the premenopausal breast, we analyzed breast tissues for expression of cell senescence biomarkers TP53, p21, and β-galactosidase (β-GAL) by IHC using specific antibodies to these proteins.…”
Section: Adipose Il10 Expression and Glandular Phenotypementioning
confidence: 99%